Coating material suitable for quartz product and preparation method thereof

By coating a coating material containing low melting point glass powder and ceramic functional additives on the surface of the quartz product, the problem of silicon deposition and erosion of quartz pipes caused by the LPCVD process is solved, and effective protection and service life of quartz products are achieved.

CN119912843AActive Publication Date: 2025-05-02TOPNENG (JIANGSU) QUARTZ TECH CO LTD

Patent Information

Application Number
CN202411874937.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-05-02
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The existing LPCVD process leads to silicon deposition on the surface of quartz pipes during silicon deposition, resulting in erosion and furnace tube explosion, reducing the service life of the pipes.

Method used

A coating material suitable for quartz products is adopted, which includes a normal temperature film forming medium, a high temperature film forming medium and ceramic functional additives. By adjusting the composition distribution ratio of low melting point glass powder, the adhesion and expansion coefficient of the coating material are adjusted, and applied to the surface of quartz products to prevent silicon corrosion and stress damage.

Benefits of technology

It effectively prevents the erosion of deposited silicon on quartz products, alleviates the stress effect of quartz and silicon deposition layers, and significantly improves the service life of quartz products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912843A_ABST
    Figure CN119912843A_ABST
Patent Text Reader

Abstract

The invention provides a coating material suitable for a quartz product and a preparation method of the coating material. The water-based coating material comprises a normal-temperature film-forming medium, a high-temperature film-forming medium, a ceramic functional additive and deionized water, the normal-temperature film-forming medium comprises a thickening binder, a dispersing agent, a defoaming agent and a flatting agent; the high-temperature film forming medium comprises low-melting-point glass powder and a high-temperature binder; the ceramic functional additive comprises silicon nitride, silicon carbide, aluminum oxide and zirconium oxide powder. The low-melting-point glass powder and the ceramic functional additive can improve the adhesive force, compactness and mechanical performance of the coating and adjust the expansion coefficient of the coating, and the room-temperature film forming medium can adjust the viscosity, fineness and the like of the coating material. And the binding force and compactness between the coating material and the quartz product can be ensured. The coating can effectively protect the quartz product, prevent erosion and stress damage of other physical or chemical processes to quartz, and prolong the service life of the quartz product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coating preparation, and in particular to a coating material suitable for quartz products and a preparation method thereof. Background Art

[0002] In the processing of photovoltaic and semiconductor products, LPCVD (Low Pressure Chemical Vapor Deposition) technology is often used. It is mainly used for material deposition processes, such as depositing oxide, nitride, polysilicon and other thin films on photovoltaic or semiconductor products.

[0003] The existing LPCVD process usually uses quartz tubes as reaction furnace tubes. During the silicon deposition process, since the deposition of the LPCVD process is not directional, a large amount of silicon will be deposited on the inner surface of the furnace tube. These deposited silicon will corrode the quartz tube, and the expansion coefficient of the silicon deposition layer is quite different from that of the quartz glass. Due to the effect of thermal stress, the furnace tube will also burst, reducing the service life of the tube. Summary of the invention

[0004] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a coating material suitable for quartz products and a preparation method thereof. The coating material has good adhesion and a low expansion coefficient. When coated on the surface of the quartz product, it can effectively prevent the deposited silicon from corroding the quartz product and relieve the stress of the quartz and silicon deposited layers.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] According to the first aspect of the present invention, a coating material suitable for quartz products is provided. The coating material suitable for quartz products comprises the following components in weight fractions: room temperature film-forming medium: 5.0% to 25.0%, high temperature film-forming medium: 3.0% to 25.0%, ceramic functional additives: 3.0% to 30.0%, and the balance is deionized water; wherein the room temperature film-forming medium comprises a thickening binder, a dispersant, a defoaming agent, and a leveling agent; the high temperature film-forming medium comprises a low melting point glass powder and a high temperature binder; and the ceramic functional additives comprise silicon nitride powder, silicon carbide powder, aluminum oxide powder, and zirconium oxide powder.

[0007] Preferably, the coating material suitable for quartz products includes the following components in weight fractions:

[0008] The proportions of the components of the room temperature film-forming medium are as follows: thickening binder: 7.0% to 20.0%; dispersant: 0.1% to 2.0%; defoamer: 0.1% to 2.0%; and leveling agent: 0.1% to 2.0%.

[0009] The proportions of the components of the high-temperature film-forming medium are as follows: low-melting-point glass powder: 2.0% to 13.0%; high-temperature adhesive: 2.0% to 12.0%.

[0010] The proportions of the components of the ceramic functional additive are as follows: silicon nitride powder: 0.5% to 7.0%; silicon carbide powder: 1.0% to 8.0%; aluminum oxide powder: 1.0% to 8.0%; zirconium oxide powder: 0.5% to 7.0%.

[0011] The balance was deionized water.

[0012] Preferably, the low-melting point glass powder is a silicon-containing system glass powder, and the low-melting point glass powder includes the following components: silicon oxide, oxide A, oxide B, oxide C, oxide D, and oxide E; wherein the weight fraction of each component is: silicon oxide: 5.0% to 50.0%, oxide A: 1.0% to 10.0%, oxide B: 1.0%-20.0%, oxide C: 1.0% to 15.0%, oxide D: 5.0% to 50.0%, and oxide E: 1.0% to 20.0%.

[0013] Preferably, the oxide A is at least one of the alkali metal oxides lithium oxide, sodium oxide, and potassium oxide; the oxide B is at least one of the alkaline earth metal oxides magnesium oxide, calcium oxide, strontium oxide, and barium oxide; the oxide C is at least one of the transition metal oxides titanium oxide, zirconium oxide, zinc oxide, and lanthanum oxide; the oxide D is at least one of the post-transition metal oxides and / or metalloid oxides lead oxide, bismuth oxide, tellurium oxide, thallium oxide, tin oxide, antimony oxide, gallium oxide, and indium oxide; the oxide E is one or two oxides of aluminum oxide and boron oxide.

[0014] Preferably, the preparation method of the low-melting-point glass powder includes: preparing raw materials in a required proportion, stirring and mixing the raw materials evenly, melting them at a high temperature of 1000°C to 1600°C in a frit furnace, and then quenching the molten glass liquid with water, drying, coarse grinding, fine grinding, and precise grading to obtain the low-melting-point glass powder.

[0015] Preferably, the high temperature binder is any one of silica sol and silicate or a combination of the two.

[0016] Preferably, the thickening binder is one or a combination of at least two of methyl cellulose, hydroxyethyl cellulose, hydroxymethyl cellulose, sodium hydroxymethyl cellulose, sodium carboxymethyl cellulose or polyacrylic thickening binders; the dispersant is any one or a combination of two of ammonium acrylate or styrene maleic anhydride modified polymer; the defoamer is any one or a combination of two of mineral oil defoamer or polyethylene glycol; the leveling agent is any one or a combination of two of polyether modified silicone or acrylic leveling agents.

[0017] According to a second aspect of the present invention, a method for preparing a coating material suitable for a quartz product is provided, the method for preparing a coating material suitable for a quartz product comprising:

[0018] Step S1: weighing a room temperature film-forming medium, a high temperature film-forming medium, a ceramic functional additive and deionized water in proportion;

[0019] Step S2: uniformly mixing deionized water and room temperature film-forming medium to obtain a first mixture;

[0020] Step S3: adding the high temperature film-forming medium and the ceramic functional additive to the first mixture, and dispersing the mixture for 20 to 40 minutes using a disperser to obtain a second mixture;

[0021] Step S4: adding deionized water to the second mixture to dilute it, then finely grinding the diluted mixture using a bead mill, and adjusting the viscosity to obtain a coating with the required viscosity and fineness;

[0022] Step S5: coating the coating with required viscosity and fineness onto the surface of the quartz product, and after drying, annealing the coated quartz product using an annealing furnace, and then cooling to room temperature.

[0023] Preferably, in step S5, the annealing temperature is 800-1100° C., and the annealing time is 0.5-3 hours.

[0024] Preferably, in step S5, the quartz product is annealed by a two-stage heating and insulation method: the first stage is heating to 300-600°C and insulation for 20-50 minutes, and the second stage is heating to 800-1100°C and insulation for 0.5-3 hours.

[0025] Preferably, in step S5, the quartz product is annealed by a three-stage heating and insulation method: the first stage is heated to 180-220°C and kept warm for 20-40 minutes, the second stage is heated to 300-600°C and kept warm for 20-50 minutes, and the third stage is heated to 800-1100°C and kept warm for 0.5-3 hours.

[0026] Compared with the prior art, the beneficial effects of the present invention are as follows: in the coating material of the present invention, by adjusting the component ratio of the low-melting-point glass powder, the melting point of the low-melting-point glass powder can be adjusted, so that the coating material and the quartz product can be well fused and bonded; and, by adjusting the component ratio of the low-melting-point glass powder, the expansion coefficient of the coating material can also be adjusted, so as to meet the application requirements of different quartz products; the combination of the low-melting-point glass powder and the ceramic functional additive can increase the adhesion between the coating material and the surface of the quartz product, improve the density and mechanical properties of the coating material, and reduce its expansion coefficient; the room temperature film-forming medium can adjust the viscosity, fineness and other properties of the coating material; the coating material is annealed and sintered after being applied to the quartz product, so as to ensure the bonding strength and density between the coating material and the quartz product, thereby effectively protecting the quartz product and preventing erosion and stress damage to the quartz by other physical or chemical processes, thereby greatly improving the service life of the quartz product. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The present invention is a flowchart of a method for preparing a coating material according to some embodiments of the present invention. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below in conjunction with the accompanying drawings of the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention. It can be understood that some technical means of the various embodiments described herein can be replaced or combined with each other without conflict.

[0029] In the description of the present invention, if there are terms such as "first", "second", etc., they are only used to distinguish the objects described, and do not have any order or technical meaning. Therefore, the objects defined as "first", "second", etc. may explicitly or implicitly include one or more of the objects. In addition, "one" or "a" and similar words do not indicate a quantity limitation, but indicate the existence of at least one, and "multiple" means not less than two.

[0030] In the description of the present specification, reference to "one embodiment" or "some embodiments" etc. means that one or more embodiments of the present invention include a specific feature, structure or characteristic described in conjunction with the embodiment. Therefore, the phrases "in one embodiment", "in some embodiments", "in some other embodiments", "in some other embodiments", etc. appearing in different places in this specification do not necessarily refer to the same embodiment, but mean "one or more but not all embodiments", unless otherwise specifically emphasized in other ways.

[0031] According to a first aspect of the present invention, there is provided a coating material suitable for quartz products. The coating material has good adhesion, mechanical strength and low expansion coefficient. When coated on the surface of the quartz product, it can effectively prevent the deposited silicon from corroding the quartz product and relieve the stress of the quartz and silicon deposited layers.

[0032] In some embodiments, the coating material suitable for quartz products includes the following components by weight (percentage of the total weight of the coating material): room temperature film-forming medium: 5.0% to 25.0%, high temperature film-forming medium: 3.0% to 25.0%, ceramic functional additives: 3.0% to 30.0%, and the balance is deionized water. Among them, the room temperature film-forming medium includes a thickening binder, a dispersant, a defoaming agent, and a leveling agent; the high temperature film-forming medium includes a low melting point glass powder and a high temperature binder; and the ceramic functional additives include silicon nitride (Si3N4) powder, silicon carbide (SiC) powder, aluminum oxide (Al2O3) powder, and zirconium oxide (ZrO2) powder.

[0033] In this coating material, the combination of low-melting-point glass powder and ceramic functional additives can increase the bonding strength between the coating and the quartz material, improve the density and mechanical properties of the coating, and reduce its expansion coefficient. The high-temperature binder enables the coating material to maintain good bonding properties in a high-temperature environment, and plays an anti-oxidation and heat-insulating role. The room-temperature film-forming medium can adjust the viscosity, fineness, etc. of the coating material. After the coating material is applied to the quartz product and annealed and sintered, it can ensure the bonding strength and density between the coating material and the quartz product, and can remain stable and not fall off at high temperatures, thereby effectively protecting the quartz product and preventing erosion and stress damage to the quartz by other physical or chemical processes, thereby greatly improving the service life of the quartz product.

[0034] In some preferred embodiments, the coating material suitable for quartz products includes the following components by weight (percentage of the total weight of the coating material):

[0035] The proportions of the components of the room temperature film-forming medium are as follows: thickening binder: 7.0% to 20.0%; dispersant: 0.1% to 2.0%; defoaming agent: 0.1% to 2.0%; leveling agent: 0.1% to 2.0%.

[0036] The proportions of the components of the high-temperature film-forming medium are as follows: low-melting-point glass powder: 2.0% to 13.0%; high-temperature binder: 2.0% to 12.0%.

[0037] The proportions of various components of the ceramic functional additive are as follows: silicon nitride powder: 0.5% to 7.0%; silicon carbide powder: 1.0% to 8.0%; aluminum oxide powder: 1.0% to 8.0%; zirconium oxide powder: 0.5% to 7.0%.

[0038] The balance was deionized water.

[0039] Among them, the role of the thickening binder is to increase the consistency of the coating material while maintaining its stable fluidity. The dispersant can make the particles break more quickly, reduce the solid-liquid interface free energy, and make the coating material dispersed evenly and stably. The defoamer can inhibit and eliminate foam to ensure the stability of the coating material. The leveling agent can improve the leveling and wettability of the coating material, reduce surface defects, and improve the quality of the coating. Low-melting point glass powder can improve the adhesion, toughness, wear resistance, heat resistance, and corrosion resistance of the coating material. The high-temperature binder enables the coating material to maintain good bonding properties under high temperature conditions, and plays an antioxidant and heat-insulating role. Silicon nitride powder, silicon carbide powder, aluminum oxide powder, and zirconium oxide powder, as ceramic functional additives, can increase the hardness of the coating material, improve the adhesion of the coating material, and improve the corrosion resistance of the coating material.

[0040] Furthermore, the preferred weight fraction of the low-melting-point glass powder (as a percentage of the total weight of the coating material) is set at 2.0% to 13.0% (as a percentage of the total weight of the coating material). Too little will not have a fusion and bonding effect, while too much will result in an excessively thick glass layer between the coating material and the quartz material, which will reduce the melting point of the quartz material at high temperatures and have an adverse effect on the coating effect.

[0041] The coating material of the present invention uses low-melting glass powder, and the micro-melting state of the low-melting glass powder can be used during the high-temperature annealing process to achieve the fusion bonding of quartz and the coating material. The advantage is that it improves the disadvantage that there is only adhesion between the coating material and the quartz glass, but no fusion bonding force, and greatly improves the adhesion of the coating material. At the same time, the elements in the low-melting glass powder can also improve the corrosion resistance of the coating. In addition, the high-temperature adhesive also plays an auxiliary bonding function, and its melting point is slightly higher than the melting point of the low-melting glass powder. It can adjust the problem of low-melting glass powder melting and flowing too fast to a certain extent, and maintain the stability of the coating material at high temperature. At the same time, the low-melting glass powder can also adjust the expansion coefficient of the coating material, and the expansion coefficient and the hardness of the coating can be adjusted by matching ceramic functional additives. The room temperature film-forming medium mainly controls the viscosity, fineness and solid content of the coating material. The preferred weight ratio of the room temperature film-forming medium in the present invention is set to 5.0% to 25.0%. If the solid content is too high or the viscosity is too high, the difficulty of spraying increases, and the uniformity is poor. If the solid content is too low or the viscosity is too low, the spraying is easy to sag.

[0042] In some preferred embodiments, the low melting point glass powder is a silicon-containing system glass powder, which has the characteristics of acid and alkali resistance, chemical inertness, low expansion coefficient, etc. The low melting point glass powder includes the following components: silicon oxide (SiO2), oxide A, oxide B, oxide C, oxide D, and oxide E. Among them, the weight fraction of each component (as a percentage of the total weight of the low melting point glass powder) is: silicon oxide: 5.0% to 50.0%, oxide A: 1.0% to 10.0%, oxide B: 1.0%-20.0%, oxide C: 1.0% to 15.0%, oxide D: 5.0% to 50.0%, oxide E: 1.0% to 20.0%.

[0043] Furthermore, oxide A is an alkali metal oxide, oxide B is an alkaline earth metal oxide, oxide C is a transition metal oxide, oxide D is a post-transition metal oxide and / or a metalloid oxide; oxide E is one or two oxides of aluminum oxide (Al2O3) and boron oxide (B2O3).

[0044] Furthermore, oxide A is at least one of the alkali metal oxides lithium oxide (Li2O), sodium oxide (Na2O), and potassium oxide (K2O); oxide B is at least one of the alkaline earth metal oxides magnesium oxide (MgO), calcium oxide (CaO), strontium oxide (SrO), and barium oxide (BaO); oxide C is at least one of the transition metal oxides titanium oxide (TiO2), zirconium oxide (ZrO2), zinc oxide (ZnO), and lanthanum oxide (LaO); oxide D is at least one of the post-transition metal oxides and / or metalloid oxides lead oxide (PbO), bismuth oxide (Bi2O3), tellurium oxide (TeO2), thallium oxide (Tl2O3), tin oxide (SnO2), antimony oxide (Sb2O3), gallium oxide (Ga2O3), and indium oxide (In2O3).

[0045] In the above-mentioned low-melting glass powder, silicon oxide, post-transition metal oxides and metalloid oxides constitute the network structure of the glass. Alkali metal oxides can adjust the viscosity of the glass at high temperature, which is conducive to better fusion and bonding with quartz products at a suitable temperature in combination with ceramic functional additives. Transition metal oxides can improve the mechanical strength of the glass and provide good thermal stability. At the same time, silicon oxide, some alkali metals and transition metal oxides can improve the expansion coefficient of the glass and the coating. Therefore, the low-melting glass powder is very important for the overall performance of the coating material. The coating material prepared by using the low-melting glass powder of the present invention, a normal temperature film-forming medium and a ceramic functional additive has good adhesion and mechanical strength, and can match the quartz material for long-term stable use at high temperature, and well protects the quartz material to prevent the quartz material from being eroded and damaged.

[0046] Among them, increasing the proportion of silicon oxide in the low-melting-point glass powder within a reasonable range can increase the melting point of the low-melting-point glass powder; reducing the proportion of silicon oxide within a reasonable range can reduce the melting point of the low-melting-point glass powder.

[0047] In some preferred embodiments, the low-melting point glass powder includes the following components in weight fraction (as a percentage of the weight of the low-melting point glass powder): silicon oxide: 10.0% to 40.0%, oxide A: 1.0% to 10.0%, oxide B: 5.0%-20.0%, oxide C: 1.0% to 10.0%, oxide D: 10.0% to 50.0%, and oxide E: 1.0% to 15.0%.

[0048] In other preferred embodiments, the low-melting point glass powder includes the following components in weight fraction (as a percentage of the weight of the low-melting point glass powder): silicon oxide: 10.0% to 40.0%; oxide A (alkali metal oxide): 1.0% to 10.0%; oxide B (alkaline earth metal oxide): 5.0%-20.0%; zinc oxide: 1.0% to 10.0%; tellurium oxide: 5.0% to 25.0%; bismuth oxide: 5.0% to 25.0%; aluminum oxide: 1.0% to 15.0%.

[0049] In some embodiments, the preparation method of the above-mentioned low-melting point glass powder includes: preparing raw materials according to the required proportions, stirring and mixing the raw materials evenly, melting them at a high temperature of 1000°C to 1600°C in a frit furnace, and then quenching the molten glass liquid with water, drying, coarse grinding, fine grinding, and precise grading to obtain low-melting point glass powder.

[0050] In some preferred embodiments, the high temperature adhesive may be any one of silica sol or silicate or a combination of the two. The high temperature adhesive enables the coating material to maintain good bonding performance in a high temperature environment, and plays an anti-oxidation and heat insulation role.

[0051] In some preferred embodiments, the thickening binder can be one or a combination of at least two of methyl cellulose, hydroxyethyl cellulose, hydroxymethyl cellulose, sodium hydroxymethyl cellulose, sodium carboxymethyl cellulose or polyacrylic thickening binders. The dispersant can be any one or a combination of acrylic acid ammonium salts or styrene maleic anhydride modified polymers. The defoamer can be any one or a combination of mineral oil defoamer or polyethylene glycol. The leveling agent can be any one or a combination of polyether modified silicone or acrylic leveling agents.

[0052] The function of thickening binder is to increase the consistency of coating materials while maintaining their stable fluidity. Dispersant can make particles break more quickly, reduce the free energy of solid-liquid interface, and make the coating materials dispersed evenly and stably. Defoamer can inhibit and eliminate foam to ensure the stability of coating materials. Leveling agent can improve the leveling and wettability of coating materials, reduce surface defects, and improve the quality of coating film.

[0053] According to a second aspect of the present invention, a method for preparing a coating material suitable for a quartz product is provided. Figure 1 As shown, in some embodiments, the method for preparing the coating material suitable for quartz products includes:

[0054] Step S1: weighing a room temperature film-forming medium, a high temperature film-forming medium, a ceramic functional additive and deionized water in proportion.

[0055] Step S2: Mix deionized water and room temperature film-forming medium evenly to obtain a first mixture.

[0056] Step S3: adding the high-temperature film-forming medium and the ceramic functional additive into the first mixture, and dispersing the mixture using a disperser for 20 minutes to 40 minutes to obtain a second mixture.

[0057] Step S4: adding deionized water to the second mixture to dilute it, then finely grinding the diluted mixture using a bead mill, and adjusting the viscosity to obtain a coating with the required viscosity and fineness.

[0058] Step S5: coating the coating with required viscosity and fineness onto the surface of the quartz product, and after drying, annealing the coated quartz product using an annealing furnace, and then cooling to room temperature.

[0059] In some preferred embodiments, the viscosity of the diluted mixed solution in step S4 can be tested by the four-cup coating method in the prior art, and the viscosity of the mixed solution can be 15s to 55s ("s" means seconds, which refers to the time required for a specific volume of coating to flow out). The fineness of the coating after fine grinding (the particle size of the coating particles) is <15μm.

[0060] In some preferred embodiments, in step S5, the annealing temperature is 800-1100° C., and the annealing time is 0.5-3 hours.

[0061] In other preferred embodiments, in step S5, the quartz product is annealed by a two-stage heating and insulation method: the first stage is heating to 300-600°C and insulation for 20-50 minutes, and the second stage is heating to 800-1100°C and insulation for 0.5-3 hours.

[0062] In some preferred embodiments, in step S5, the quartz product is annealed by a three-stage heating and heat preservation method: the first stage is heated to 180-220°C and kept warm for 20-40 minutes, the second stage is heated to 300-600°C and kept warm for 20-50 minutes, and the third stage is heated to 800-1100°C and kept warm for 0.5-3 hours. The three-stage heating and heat preservation method is used to anneal the quartz product, which can fully volatilize the solvent and fully remove the binder at the medium and low temperature stages, obtain a good annealing effect, enhance the bonding strength and density of the coating material and the quartz product, and improve the comprehensive performance of the coating material.

[0063] In the above-mentioned coating materials, low-melting-point glass powder and ceramic functional additives can improve the mechanical properties of the coating and reduce its expansion coefficient. The organic functional phase and surfactant can adjust the viscosity, fineness, etc. of the coating material. After the coating material is applied to the quartz product and then annealed and sintered, the bonding strength and density between the coating material and the quartz product can be ensured, thereby effectively protecting the quartz product and preventing erosion and stress damage to the quartz by other physical or chemical process processes, thereby greatly improving the service life of the quartz product.

[0064] The following are 7 specific embodiments of the present invention and 1 comparative example. In each embodiment, a coating is prepared by adopting a set component ratio and a preparation method, and after the coating is applied to the inner walls of 10 quartz tube products of the same batch and model, an annealing treatment is performed to form a coating on the inner wall of the quartz tube. Afterwards, the average service life of the 10 quartz tubes is tested and counted. Among them, the coating thickness of the coating in each embodiment is consistent; the average service life of the quartz tube can be used to characterize the protective ability of the coating material to the quartz tube. In the comparative example, none of the 10 quartz tubes are coated with the coating.

[0065] Table 1 shows the weight ratio of each component in the coating material in Example 1, Example 2A, Example 3 and Example 4:

[0066] Table 1

[0067]

[0068] Table 2 shows the weight ratio of each component in the coating material in Example 5, Example 6 and Example 2B:

[0069] Table 2

[0070]

[0071]

[0072] Table 3 shows the performance test results of the coating materials applied to the quartz tube products in the seven embodiments and the performance test results of the uncoated quartz tube product in Comparative Example 1:

[0073] Table 3

[0074] variable Average service life of quartz tube (days) Example 1 Low melting point glass powder 1 111 Example 2A Low melting point glass powder 2 276 Example 3 Low melting point glass powder 2-low content 134 Example 4 Low melting point glass powder 2-high content 137 Example 5 High temperature binder - low content 201 Example 6 High temperature binder - high content 206 Example 2B One stage heating process 218 Comparative Example 1 No coating 101

[0075] Embodiment 1:

[0076] The weight fraction of each component in the coating material is: thickening binder: 15.00%, dispersant: 0.50%, leveling agent: 0.50%, defoaming agent: 0.50%, low melting point glass powder 1: 5.00%, high temperature binder: 4.00%, silicon nitride: 2.00%, silicon carbide: 3.00%, aluminum oxide: 3.00%, zirconium oxide: 1.00%, and deionized water: 65.50%.

[0077] The weight fractions of the components in the low-melting glass powder 1 are as follows: silicon oxide: 38.0%; oxide A: 4.0%; oxide B: 12.0%; oxide C: 5.0%; oxide D: 31.0%; oxide E: 10.0%. The proportion of silicon oxide in the low-melting glass powder 1 is slightly higher, and the melting point of the low-melting glass powder 1 is 200-900°C.

[0078] The method for preparing the coating material comprises:

[0079] Step S1: weigh the room temperature film-forming medium, the high temperature film-forming medium, the ceramic functional additive and deionized water according to the proportions of Example 1 in Table 1.

[0080] Step S2: Mix deionized water and room temperature film-forming medium evenly to obtain a first mixture.

[0081] Step S3: adding the high-temperature film-forming medium and the ceramic functional additive into the first mixture, and dispersing the mixture using a disperser for 20 minutes to 40 minutes to obtain a second mixture.

[0082] Step S4: deionized water is added to the second mixture to dilute it, and then the diluted mixture is finely ground using a bead mill, and the viscosity is adjusted to obtain a coating with a fineness of 10 μm and a viscosity of 40 s.

[0083] Step S5: Apply the coating to the surface of the quartz product, and after drying, use an annealing furnace to anneal the coated quartz product, and then cool it to room temperature. The quartz product is annealed in a three-stage heating and insulation method: the first stage is heated to 200°C and kept warm for 30 minutes, the second stage is heated to 400°C and kept warm for 30 minutes, and the third stage is heated to 1000°C and kept warm for 0.5 to 3 hours.

[0084] After testing, the expansion coefficient of the coating prepared by the composition ratio and preparation method of Example 1 is 1.56×10 - 6 K-1 The average service life of the quartz tube is 111 days.

[0085] Example 2A:

[0086] The weight fraction of each component in the coating material is: thickening binder: 15.00%, dispersant: 0.50%, leveling agent: 0.50%, defoaming agent: 0.50%, low melting point glass powder 2: 5.00%, high temperature binder: 4.00%, silicon nitride: 2.00%, silicon carbide: 3.00%, aluminum oxide: 3.00%, zirconium oxide: 1.00%, and deionized water: 65.50%.

[0087] The weight ratio of the components in the low-melting-point glass powder 2 is: silicon oxide: 28.0%; oxide A: 5.0%; oxide B: 15.0%; oxide C: 6.0%; oxide D: 35.0%; oxide E: 11.0%. Compared with the low-melting-point glass powder 1, the proportion of silicon oxide in the low-melting-point glass powder 2 is slightly lower, and the melting point of the low-melting-point glass powder 2 is 200-800°C, which is slightly lower than the melting point of the low-melting-point glass powder 1.

[0088] The method for preparing the coating material comprises:

[0089] Step S1: weigh the room temperature film-forming medium, the high temperature film-forming medium, the ceramic functional additive and deionized water according to the proportions of Example 2A in Table 1.

[0090] Step S2: Mix deionized water and room temperature film-forming medium evenly to obtain a first mixture.

[0091] Step S3: adding the high-temperature film-forming medium and the ceramic functional additive into the first mixture, and dispersing the mixture using a disperser for 20 minutes to 40 minutes to obtain a second mixture.

[0092] Step S4: deionized water is added to the second mixture to dilute it, and then the diluted mixture is finely ground using a bead mill, and the viscosity is adjusted to obtain a coating with a fineness of 10 μm and a viscosity of 40 s.

[0093] Step S5: Apply the coating to the surface of the quartz product, and after drying, use an annealing furnace to anneal the coated quartz product, and then cool it to room temperature. The quartz product is annealed in a three-stage heating and insulation method: the first stage is heated to 200°C and kept warm for 30 minutes, the second stage is heated to 400°C and kept warm for 30 minutes, and the third stage is heated to 1000°C and kept warm for 0.5 to 3 hours.

[0094] After testing, the expansion coefficient of the coating prepared by the composition ratio and preparation method of Example 2A is 1.65×10 -6 K -1The average service life of the quartz tube is 276 days.

[0095] Embodiment 3:

[0096] The weight fraction of each component in the coating material is: thickening binder: 15.00%, dispersant: 0.50%, leveling agent: 0.50%, defoaming agent: 0.50%, low melting point glass powder 2: 3.00%, high temperature binder: 4.00%, silicon nitride: 2.44%, silicon carbide: 3.67%, aluminum oxide: 3.67%, zirconium oxide: 1.22%, and deionized water: 65.50%.

[0097] The weight ratio of the components in the low-melting-point glass powder 2 is: silicon oxide: 28.0%; oxide A: 5.0%; oxide B: 15.0%; oxide C: 6.0%; oxide D: 35.0%; oxide E: 11.0%. The melting point of the low-melting-point glass powder 2 is 200-800°C.

[0098] The method for preparing the coating material comprises:

[0099] Step S1: weigh the room temperature film-forming medium, the high temperature film-forming medium, the ceramic functional additive and deionized water according to the proportions of Example 3 in Table 1.

[0100] Step S2: Mix deionized water and room temperature film-forming medium evenly to obtain a first mixture.

[0101] Step S3: adding the high-temperature film-forming medium and the ceramic functional additive into the first mixture, and dispersing the mixture using a disperser for 20 minutes to 40 minutes to obtain a second mixture.

[0102] Step S4: deionized water is added to the second mixture to dilute it, and then the diluted mixture is finely ground using a bead mill, and the viscosity is adjusted to obtain a coating with a fineness of 10 μm and a viscosity of 40 s.

[0103] Step S5: Apply the coating to the surface of the quartz product, and after drying, use an annealing furnace to anneal the coated quartz product, and then cool it to room temperature. The quartz product is annealed in a three-stage heating and insulation method: the first stage is heated to 200°C and kept warm for 30 minutes, the second stage is heated to 400°C and kept warm for 30 minutes, and the third stage is heated to 1000°C and kept warm for 0.5 to 3 hours.

[0104] After testing, the expansion coefficient of the coating prepared by the component ratio and preparation method of Example 3 is 2.37×10 - 6 K -1 The average service life of a quartz tube is 134 days.

[0105] Embodiment 4:

[0106] The weight fraction of each component in the coating material is: thickening binder: 15.00%, dispersant: 0.50%, leveling agent: 0.50%, defoaming agent: 0.50%, low melting point glass powder 2: 7.00%, high temperature binder: 4.00%, silicon nitride: 1.56%, silicon carbide: 2.33%, aluminum oxide: 2.33%, zirconium oxide: 0.78%, and deionized water: 65.50%.

[0107] The weight ratio of the components in the low-melting-point glass powder 2 is: silicon oxide: 28.0%; oxide A: 5.0%; oxide B: 15.0%; oxide C: 6.0%; oxide D: 35.0%; oxide E: 11.0%. The melting point of the low-melting-point glass powder 2 is 200-800°C.

[0108] The method for preparing the coating material comprises:

[0109] Step S1: weigh the room temperature film-forming medium, the high temperature film-forming medium, the ceramic functional additive and deionized water according to the proportions of Example 4 in Table 1.

[0110] Step S2: Mix deionized water and room temperature film-forming medium evenly to obtain a first mixture.

[0111] Step S3: adding the high-temperature film-forming medium and the ceramic functional additive into the first mixture, and dispersing the mixture using a disperser for 20 minutes to 40 minutes to obtain a second mixture.

[0112] Step S4: deionized water is added to the second mixture to dilute it, and then the diluted mixture is finely ground using a bead mill, and the viscosity is adjusted to obtain a coating with a fineness of 10 μm and a viscosity of 39 s.

[0113] Step S5: Apply the coating to the surface of the quartz product, and after drying, use an annealing furnace to anneal the coated quartz product, and then cool it to room temperature. The quartz product is annealed in a three-stage heating and insulation method: the first stage is heated to 200°C and kept warm for 30 minutes, the second stage is heated to 400°C and kept warm for 30 minutes, and the third stage is heated to 1000°C and kept warm for 0.5 to 3 hours.

[0114] After testing, the expansion coefficient of the coating prepared by the composition ratio and preparation method of Example 4 is 2.81×10 - 6 K -1 The average service life of the quartz tube is 137 days.

[0115] Embodiment 5:

[0116] The weight fraction of each component in the coating material is: thickening binder: 15.00%, dispersant: 0.50%, leveling agent: 0.50%, defoaming agent: 0.50%, low melting point glass powder 2: 5.00%, high temperature binder: 2.50%, silicon nitride: 2.33%, silicon carbide: 3.50%, aluminum oxide: 3.50%, zirconium oxide: 1.17%, and deionized water: 65.50%.

[0117] The weight ratio of the components in the low-melting-point glass powder 2 is: silicon oxide: 28.0%; oxide A: 5.0%; oxide B: 15.0%; oxide C: 6.0%; oxide D: 35.0%; oxide E: 11.0%. The melting point of the low-melting-point glass powder 2 is 200-800°C.

[0118] The method for preparing the coating material comprises:

[0119] Step S1: weigh the room temperature film-forming medium, the high temperature film-forming medium, the ceramic functional additive and deionized water according to the proportions of Example 5 in Table 2.

[0120] Step S2: Mix deionized water and room temperature film-forming medium evenly to obtain a first mixture.

[0121] Step S3: adding the high-temperature film-forming medium and the ceramic functional additive into the first mixture, and dispersing the mixture using a disperser for 20 minutes to 40 minutes to obtain a second mixture.

[0122] Step S4: deionized water is added to the second mixture to dilute it, and then the diluted mixture is finely ground using a bead mill, and the viscosity is adjusted to obtain a coating with a fineness of 10 μm and a viscosity of 39 s.

[0123] Step S5: Apply the coating to the surface of the quartz product, and after drying, use an annealing furnace to anneal the coated quartz product, and then cool it to room temperature. The quartz product is annealed in a three-stage heating and insulation method: the first stage is heated to 200°C and kept warm for 30 minutes, the second stage is heated to 400°C and kept warm for 30 minutes, and the third stage is heated to 1000°C and kept warm for 0.5 to 3 hours.

[0124] After testing, the expansion coefficient of the coating prepared by the composition ratio and preparation method of Example 5 is 2.28×10 - 6 K -1 The average service life of the quartz tube is 201 days.

[0125] Embodiment 6:

[0126] The weight fraction of each component in the coating material is: thickening binder: 15.00%, dispersant: 0.50%, leveling agent: 0.50%, defoaming agent: 0.50%, low melting point glass powder 2: 5.00%, high temperature binder: 5.50%, silicon nitride: 1.67%, silicon carbide: 2.50%, aluminum oxide: 2.50%, zirconium oxide: 0.83%, and deionized water: 65.50%.

[0127] The weight ratio of the components in the low-melting-point glass powder 2 is: silicon oxide: 28.0%; oxide A: 5.0%; oxide B: 15.0%; oxide C: 6.0%; oxide D: 35.0%; oxide E: 11.0%. The melting point of the low-melting-point glass powder 2 is 200-800°C.

[0128] The method for preparing the coating material comprises:

[0129] Step S1: weigh the room temperature film-forming medium, the high temperature film-forming medium, the ceramic functional additive and deionized water according to the proportions of Example 6 in Table 2.

[0130] Step S2: Mix deionized water and room temperature film-forming medium evenly to obtain a first mixture.

[0131] Step S3: adding the high-temperature film-forming medium and the ceramic functional additive into the first mixture, and dispersing the mixture using a disperser for 20 minutes to 40 minutes to obtain a second mixture.

[0132] Step S4: deionized water is added to the second mixture to dilute it, and then the diluted mixture is finely ground using a bead mill, and the viscosity is adjusted to obtain a coating with a fineness of 10 μm and a viscosity of 40 s.

[0133] Step S5: Apply the coating to the surface of the quartz product, and after drying, use an annealing furnace to anneal the coated quartz product, and then cool it to room temperature. The quartz product is annealed in a three-stage heating and insulation method: the first stage is heated to 200°C and kept warm for 30 minutes, the second stage is heated to 400°C and kept warm for 30 minutes, and the third stage is heated to 1000°C and kept warm for 0.5 to 3 hours.

[0134] After testing, the expansion coefficient of the coating prepared by the component ratio and preparation method of Example 6 is 2.13×10 - 6 K -1 The average service life of the quartz tube is 206 days.

[0135] Example 2B:

[0136] The weight fraction of each component in the coating material is the same as that in Example 2A: thickening binder: 15.00%, dispersant: 0.50%, leveling agent: 0.50%, defoaming agent: 0.50%, low melting point glass powder 2: 5.00%, high temperature binder: 4.00%, silicon nitride: 2.00%, silicon carbide: 3.00%, aluminum oxide: 3.00%, zirconium oxide: 1.00%, and deionized water: 65.50%.

[0137] The weight ratio of the components in the low-melting-point glass powder 2 is: silicon oxide: 28.0%; oxide A: 5.0%; oxide B: 15.0%; oxide C: 6.0%; oxide D: 35.0%; oxide E: 11.0%. The melting point of the low-melting-point glass powder 2 is 200-800°C.

[0138] The method for preparing the coating material comprises:

[0139] Step S1: weigh the room temperature film-forming medium, the high temperature film-forming medium, the ceramic functional additive and deionized water according to the proportions of Example 2B in Table 2.

[0140] Step S2: Mix deionized water and room temperature film-forming medium evenly to obtain a first mixture.

[0141] Step S3: adding the high-temperature film-forming medium and the ceramic functional additive into the first mixture, and dispersing the mixture using a disperser for 20 minutes to 40 minutes to obtain a second mixture.

[0142] Step S4: deionized water is added to the second mixture to dilute it, and then the diluted mixture is finely ground using a bead mill, and the viscosity is adjusted to obtain a coating with a fineness of 10 μm and a viscosity of 40 s.

[0143] Step S5: Apply the coating to the surface of the quartz product, and after drying, use an annealing furnace to anneal the coated quartz product, and then cool it to room temperature, wherein the annealing temperature is 1000° C. and the annealing time is 0.5 to 3 hours.

[0144] After testing, the expansion coefficient of the coating prepared by the composition ratio and preparation method of Example 2B is 1.70×10 -6 K -1 The average service life of the quartz tube is 218 days.

[0145] Comparative Example 1: 10 quartz tubes were used directly without being coated with coating materials, and the average service life of the quartz tubes was measured to be 101 days.

[0146] By comparing Example 2A with Comparative Example 1, it can be seen that after the coating material and preparation method of the present invention are applied to quartz products, they can effectively protect the quartz products and prevent erosion and stress damage to the quartz products by other physical or chemical processes, thereby greatly improving the service life of the quartz products.

[0147] By comparing the above Example 1 with Example 2A, it can be seen that when the weight of other components in the low-melting glass powder remains unchanged, increasing the proportion of silicon oxide within a reasonable range can increase the melting point of the low-melting glass powder. When the proportion of other components in the coating material and the preparation method remain unchanged, the comprehensive performance (average service life of the product) of the coating material prepared by using the low-melting glass powder 2 with a lower melting point is higher than the comprehensive performance of the coating material prepared by the low-melting glass powder 1.

[0148] Examples 2A to 6 all use low-melting-point glass powder 2 with the same composition.

[0149] Compared with Example 2A, the proportion of low-melting glass powder 2 is reduced in Example 3, and the proportion of low-melting glass powder 2 is increased in Example 4, but the comprehensive performance of the coatings in Examples 3 and 4 is lower than that in Example 2A. Therefore, the proportion of low-melting glass powder in the coating material needs to be controlled within an appropriate range to ensure that the coating has better comprehensive performance.

[0150] Compared with Example 2A, the proportion of high-temperature adhesive in Example 5 is reduced, and the service life of the product is reduced; the proportion of high-temperature adhesive in Example 6 is increased, and the service life of the product is also reduced.

[0151] Example 2B uses the same component ratio and steps S1 to S4 as Example 2A. The difference is that in step S5 of Example 2A, a three-stage heating and heat preservation method is used for annealing; in step S5 of Example 2B, a one-stage annealing method is used. Comparing the test results of the two, it can be seen that the use of a multi-stage heating and heat preservation method to anneal the quartz product can obtain a good annealing effect and improve the comprehensive performance of the coating material.

[0152] Therefore, in practical applications, according to different application scenarios, different component ratios can be adjusted within a reasonable range to meet requirements such as melting point and coating expansion coefficient.

[0153] In the coating material of the present invention, the melting point of the low-melting-point glass powder can be adjusted by adjusting the component ratio of the low-melting-point glass powder, so that the coating material and the quartz product can be well fused and bonded; moreover, the adhesion and expansion coefficient of the coating material can also be adjusted by adjusting the component ratio of the low-melting-point glass powder, so as to meet the application requirements of different quartz products; the combination of the low-melting-point glass powder and the ceramic functional additive can increase the adhesion between the coating material and the surface of the quartz product, improve the density and mechanical properties of the coating material, and reduce its expansion coefficient; the room temperature film-forming medium can adjust the viscosity, fineness and other properties of the coating material; the coating material is annealed and sintered after being applied to the quartz product, so as to ensure the bonding strength and density between the coating material and the quartz product, so as to effectively protect the quartz product, prevent the erosion and stress damage of the quartz by other physical or chemical processes, and thus greatly improve the service life of the quartz product.

[0154] The present invention has been described by the above-mentioned relevant embodiments, however, the above-mentioned embodiments are only examples for implementing the present invention. It must be pointed out that the disclosed embodiments do not limit the scope of the present invention. On the contrary, changes and modifications made without departing from the spirit and scope of the present invention are all within the scope of patent protection of the present invention.

Claims

1. A coating material suitable for quartz products, characterized in that: The coating material suitable for quartz products includes the following components in weight fractions: room temperature film-forming medium: 5.0% to 25.0%, high temperature film-forming medium: 3.0% to 25.0%, ceramic functional additives: 3.0% to 30.0%, and the balance is deionized water; wherein the room temperature film-forming medium includes a thickening binder, a dispersant, a defoaming agent and a leveling agent; the high temperature film-forming medium includes a low melting point glass powder and a high temperature binder; and the ceramic functional additives include silicon nitride powder, silicon carbide powder, aluminum oxide powder and zirconium oxide powder.

2. The coating material suitable for quartz products according to claim 1, characterized in that: The coating material suitable for quartz products includes the following components by weight: The proportion of each component of the room temperature film-forming medium: Thickening binder: 7.0%~20.0%; Dispersant: 0.1%~2.0%; Defoaming agent: 0.1%~2.0%; Leveling agent: 0.1%~2.0%; The proportion of each component of the high temperature film-forming medium: Low melting point glass powder: 2.0%~13.0%; High temperature binder: 2.0%~12.0%; The proportion of each component of the ceramic functional additive: Silicon nitride powder: 0.5% to 7.0%; Silicon carbide powder: 1.0% to 8.0%; Alumina powder: 1.0%~8.0%; Zirconia powder: 0.5%~7.0%; The balance was deionized water.

3. The coating material suitable for quartz products according to claim 1, characterized in that: The low-melting-point glass powder is a silicon-containing system glass powder, and the low-melting-point glass powder includes the following components: silicon oxide, oxide A, oxide B, oxide C, oxide D, and oxide E; wherein the weight fraction of each component is: silicon oxide: 5.0% to 50%, oxide A: 1.0% to 10%, oxide B: 1.0%-20%, oxide C: 1.0% to 15.0%, oxide D: 5.0% to 50.0%, and oxide E: 1.0% to 20.0%.

4. The coating material suitable for quartz products according to claim 3, characterized in that: The oxide A is at least one of the alkali metal oxides lithium oxide, sodium oxide, and potassium oxide; the oxide B is at least one of the alkaline earth metal oxides magnesium oxide, calcium oxide, strontium oxide, and barium oxide; the oxide C is at least one of the transition metal oxides titanium oxide, zirconium oxide, zinc oxide, and lanthanum oxide; the oxide D is at least one of the post-transition metal oxides and / or metalloid oxides lead oxide, bismuth oxide, tellurium oxide, thallium oxide, tin oxide, antimony oxide, gallium oxide, and indium oxide; the oxide E is one or two oxides of aluminum oxide and boron oxide.

5. The coating material suitable for quartz products according to claim 3, characterized in that: The preparation method of the low-melting-point glass powder comprises: preparing raw materials according to the required proportion, stirring and mixing the raw materials evenly, melting them at a high temperature of 1000° C. to 1600° C. in a frit furnace, and then subjecting the molten glass liquid to water quenching, drying, coarse grinding, fine grinding, and precise grading to obtain the low-melting-point glass powder.

6. The coating material suitable for quartz products according to claim 1, characterized in that: The high temperature adhesive is any one of silica sol and silicate or a combination of the two.

7. The coating material suitable for quartz products according to claim 1, characterized in that: The thickening binder is one or a combination of at least two of methyl cellulose, hydroxyethyl cellulose, hydroxymethyl cellulose, sodium hydroxymethyl cellulose, sodium carboxymethyl cellulose or polyacrylic acid thickening binders; the dispersant is any one or a combination of two of ammonium acrylate or styrene maleic anhydride modified polymer; the defoamer is any one or a combination of two of mineral oil defoamer or polyethylene glycol; the leveling agent is any one or a combination of two of polyether modified silicone or acrylic leveling agents.

8. A method for preparing a coating material suitable for quartz products according to any one of claims 1 to 7, characterized in that: The method for preparing the coating material suitable for quartz products comprises: Step S1: weighing a room temperature film-forming medium, a high temperature film-forming medium, a ceramic functional additive and deionized water in proportion; Step S2: uniformly mixing deionized water and room temperature film-forming medium to obtain a first mixture; Step S3: adding the high temperature film-forming medium and the ceramic functional additive to the first mixture, and dispersing the mixture for 20 to 40 minutes using a disperser to obtain a second mixture; Step S4: adding deionized water to the second mixture to dilute it, then finely grinding the diluted mixture using a bead mill, and adjusting the viscosity to obtain a coating with the required viscosity and fineness; Step S5: coating the coating with required viscosity and fineness onto the surface of the quartz product, and after drying, annealing the coated quartz product using an annealing furnace, and then cooling to room temperature.

9. The method for preparing a coating material suitable for quartz products according to claim 8, characterized in that: In step S5, the quartz product is annealed by a three-stage heating and insulation method: the first stage is heated to 180-220°C and kept warm for 20-40 minutes, the second stage is heated to 300-600°C and kept warm for 20-50 minutes, and the third stage is heated to 800-1100°C and kept warm for 0.5-3 hours.

Citation Information

Patent Citations

  • Superfine silicate glass powder and preparation method thereof

    CN112499977A

  • Glass powder and preparation method thereof and battery silver paste with wide application window

    CN113979641A

  • Inorganic high-temperature-resistant non-stick ceramic coating as well as preparation method and application thereof

    CN115353756A

  • Water-based glass ceramic functional ceramic coating as well as preparation method and application thereof

    CN115678320A

Cited By

  • Kitchen ware and preparation method thereof

    CN122229319A

  • Cookware and method of making same

    CN122229319B